جودة الأحكام القضائية الإدارية ودورها في تحقيق الأمن القضائي في الجزائر - جروني, عبد الناصر; قسوم, عبد المالك; بوقصبة, عيسى (University of Eloued جامعة الوادي, 2023)
The quality of administrative judicial rulings is a right for individuals or litigants before it is a professional duty for the judge and an endeavor for the judicial facility, is classified among the basic principles and rules that enhance confidence in the judiciary or justice system, and the real guarantee that Is resorted to as a means to achieve judicial security. The improvement of administrative judicial rulings is considered as judicial act that requires respect for the indicators and principles stipulated in most constitutions, especially those relating to the rights of individuals. The Algerian legislator has sought, through various legal regulations, to improve the quality of administrative judicial rulings by facilitating litigation procedures and their cost, respecting the right of defense and speeding the settlement of disputes brought before the administrative judiciary, considering the rulings issued by it as the natural end to a dispute in which the country is one of its parties, With the aim of enhancing the confidence of individuals in the judicial authority to achieve judicial security, which in turn establishes the rule of law.جودة الأحكام القضائية الإدارية حق للأفراد أو المتقاضين قبل أن تكون واجباً مهنياً للقاضي واجتهاداً للمرفق القضائي، وتصنف ضمن المبادئ والقواعد الأساسية التي تعزز الثقة في القضاء أو نظام العدالة، الضمانة الحقيقية التي يتم اللجوء إليها كوسيلة لتحقيق الأمن القضائي. يعتبر تحسين الأحكام القضائية الإدارية عملاً قضائياً يتطلب احترام المؤشرات والمبادئ المنصوص عليها في معظم الدساتير، وخاصة تلك المتعلقة بحقوق الأفراد. سعى المشرع الجزائري عبر مختلف اللوائح القانونية إلى تحسين جودة الأحكام القضائية الإدارية من خلال تيسير إجراءات التقاضي وتكاليفها، واحترام حق الدفاع، وسرعة الفصل في المنازعات المرفوعة أمام القضاء الإداري، مع مراعاة الأحكام الصادرة عنه. باعتبارها النهاية الطبيعية لنزاع تكون الدولة أحد أطرافه، بهدف تعزيز ثقة الأفراد في السلطة القضائية لتحقيق الأمن القضائي الذي بدوره يرسخ سيادة القانون.
مذكرة ماستر
Keywords: Criminal security - judicial rulings; الامن القضائي -الاحكام القضائية